Momentum in Australian style portfolios: risk or inefficiency?. (9th March 2015) - Chan, Howard; Docherty, Paul
Abstract: Momentum strategies have been reported to be successful across a range of different markets and asset classes. Three possible explanations for momentum have been hypothesised: risk, return continuation and excessive co‐movement of stock returns compared with dividends. Lewellen (2002) adds to this literature by providing evidence of strong momentum returns in style portfolios that can be explained by negative cross‐serial correlation, a result which supports the excess co‐movement hypothesis. We report robust evidence of style momentum in the Australian market and use the Jegadeesh and Titman (1995) return decomposition to show that this momentum strategy is predominately explained by positive autocorrelation. Our results support the return continuation hypothesis and confirm Chen and Hong's (2002) assertion that Lewellen's (2002) explanation of style momentum returns does not stand up out‐of‐sample.